PENGARUH KUALITAS PELAYANAN, SOSIALISASI, SANKSI PERPAJAKAN, DAN LINGKUNGAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PROFESIONALISME ACCOUNT REPRESENTATIVE SEBAGAI VARIABEL MODERATING PADA KANTOR PELAYANAN PAJAK MADYA PEKANBARU - Sitio, Silvia Fransisca; Zulfadil, Zulfadil (Jurnal Tepak Manajemen Bisnis, 2017)
The objective of the research was to reveal and to analyze the influence ofservice quality, socialization, taxation sanction, and environment on taxpayersâcompliance directly and through account representative professionalism as moderatingvariable which could strengthen and weaken taxpayersâ compliance.Primary data were gathered by using questionnaires as a mean to prove the result. Thesubjects were 1023 Personal Taxpayers registered in Madya Tax Service Office,Pekanbaru, and 91 of them were used as the samples, taken by using purposivesampling technique. The data were analyzed by using Structural Equation Modeling(SEM) and Smart PLS (Partial Least Square) software program.The result of the research showed that the variables of service quality, socialization,and taxation sanction had positive and significant correlation with taxpayersâcompliance, while the variable of environment did not. It could be concluded that theincrease in the implementation of service quality, socialization, and taxation sanctionwould increase taxpayersâ compliance at the Madya Tax Service Office in Pekanbaru,but in the variable of environment this condition would not occur. The result of theresearch, using moderating variable, showed that there was positive and significantcorrelation of account representative professionalism in moderating the influence ofsocialization and taxation sanction on taxpayersâ compliance which indicated that therewas the increase in the implementation of account representative professionalism inmoderating the influence of socialism and taxation sanction on the increase intaxpayersâ compliance. For the variables of service quality and environment, accountrepresentative professionalism did not moderate the influence of service quality andenvironment on taxpayersâ compliance which indicated that the increase in theimplementation of account representative professionalism did not moderate theinfluence of service quality and environment on the increase in taxpayersâ compliance